2016
DOI: 10.1177/1049732316648128
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Help From Everyone and No-One

Abstract: Online help-seeking is an emerging trend within the 21st century. Yet, despite some movement toward developing online services, little is known about how young people locate, access, and receive support online. This study aims to conceptualize the process of online help-seeking among adolescent males. Modified photo-elicitation techniques were employed within eight semi-structured focus group sessions with adolescent males aged 14 to 15 years (n = 56) across seven schools in Northern Ireland. Thematic analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
(42 reference statements)
4
31
0
Order By: Relevance
“…Stigma-related concerns were also mitigated by specific assurances about confidentiality and the development of trust in relationships with intervention providers. This corresponds with previous reports of stigma-related concerns in other service settings (Best et al, 2016;Buchholz et al, 2015;Gronholm et al, 2017).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Stigma-related concerns were also mitigated by specific assurances about confidentiality and the development of trust in relationships with intervention providers. This corresponds with previous reports of stigma-related concerns in other service settings (Best et al, 2016;Buchholz et al, 2015;Gronholm et al, 2017).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…In addition, the internet is increasingly used as a source of help, however, little is known about the online help-seeking behavior of adolescents [20]. Best et al [21] found a difference between informal and formal online help-seeking pathways. Informal online help-seeking pathways in adolescent males reduced stigma and increased the opportunity for social support, but simultaneously reduced anonymity and control.…”
Section: Introductionmentioning
confidence: 99%
“…Informal online help-seeking pathways in adolescent males reduced stigma and increased the opportunity for social support, but simultaneously reduced anonymity and control. In contrast, formal online help-seeking pathways increased anonymity, but concurrently, they also raised concerns on the abilities of adolescents to locate and assess the quality of the information correctly [21].…”
Section: Introductionmentioning
confidence: 99%
“…Increased self-disclosure in turn predicts having higher quality friendships (Valkenburg & Peter, 2009). Some adolescents identify that online selfdisclosure protects them from feeling vulnerable when discussing their feelings, while the asynchronous nature of digital communication offers them more control over their expressions (Best et al, 2016;Nesi et al, 2018;Vermeulen et al, 2018a). Thus, for some adolescents, a perception of reduced interpersonal costs (Lim et al, 2013) or reduced stigma (DeAndrea, 2015) may facilitate digital support seeking.…”
Section: Why Might Adolescent Girls Use Digital Media To Seek Support?mentioning
confidence: 99%
“…Cooper et al, 2016;Nesi et al, 2018), adolescents may also be concerned about their support seeking attempts being shared with others. Indeed, the potential for disclosure of personal information to unintended others has been identified as a salient concern by adolescents in several studies (Best et al, 2016;Vermeulen et al, 2018a). It is unknown, however, whether trust concerns influence adolescent girls' digital support seeking behaviours.…”
Section: Potential Limitations For Adolescent Girls Seeking Support Umentioning
confidence: 99%